Anthropology Needs Bees - Sulima, Roch (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
Reviev: Karolina Echaust, Ludzie i pszczoły. Antropologia polskiego bartnictwa, Wydawnictwo Naukowe Scholar, Warszawa 2025.